Analisis Fungsi Pelatihan Terhadap Peningkatan Produktivitas Kerja Karyawan Bagian Distribusi: PT. PLN (persero) area singosari - Budi Iriani Yudaningrum; Indah Datin Nadliroh; Mifthakhun Nuha Khairudin (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2022)
This research analyzes the effect of training on the productivity of distribution employees at PT. PLN (Persero) Singosari Area. The research was conducted on all 50 employees of the Distribution Department of PT. PLN (Persero) Singosari Area. The analysis method used is the Chi-Square test with two categories. Based on the results of the Chi-Square analysis, it can be seen that training has an effect on work productivity. This is shown by the Chi-Square calculation value of 8.916 which is greater than the Chi-Square table value of 3.841 and the probability value of 0.003, which is smaller than the alpha value of 0.05, which means that Ho is rejected and Ha is the result of the hypothesis test shows that there is an effect between the amount of training and the productivity of employees in the distribution department at PT. PLN (Persero) Singosari Area.